How do local differences in saltmarsh ecology influence disease vector mosquito populations?. Issue 3 (20th February 2020) - Rowbottom, R.; Carver, S.; Barmuta, L. A.; Weinstein, P.; Allen, G. R.
Abstract: Saltmarsh breeding mosquitoes are an important source of vectors for arboviral transmission. In southern Australia, the most prominent vector borne disease, Ross River virus (Togaviridae: Alphavirus ) (RRV), is transmitted by the saltmarsh mosquito (Diptera: Culicidae) Aedes camptorhynchus (Thomson). However, the factors driving the abundance of this mosquito within and among saltmarshes are poorly understood. To predict the abundance of this mosquito within saltmarshes, the environmental conditions and aquatic invertebrate ecology of three temperate saltmarshes habitats were monitored over two seasons. Up to 44% of first‐instar mosquito numbers and 21% of pupal numbers were accounted for by environmental variables. Samphire vegetation cover was a common predictor of first‐instar numbers across sites although, between saltmarshes, aquatic factors such as high salinity, temperatures less than 22 °C and water body volume were important predictors. The identified predictors of pupal numbers were more variable and included high tides, waterbody volume and alkalinity. The composition of invertebrate functional feeding groups differed between saltmarshes and showed that an increased diversity led to fewer mosquitoes. It was evident that apparently similar saltmarshes can vary markedly in invertebrate assemblages, water availability and conditions through tidal inundations, rainfall or waterbody permanency. The present study advances insight into predictors of vector mosquito numbers that drive the risk of RRV outbreaks. Abstract : Young larval mosquito numbers were best predicted across sites by environmental variables such as samphire vegetation, although between saltmarshes predictors were based on aquatic factors including salinity and temperature. High tide, waterbody volume and alkalinity best predicted pupal mosquito numbers, although there was greater variability both within sites and across saltmarshes. Sites differed with both mosquito numbers and other aquatic invertebrates, with consistently more mosquitoes being observed at sites with less ecological diversity.